Radically Early College Entrants on Radically Early College Entrance: A Heuristic Inquiry. (December 2019) - Jett, Noel; Rinn, Anne N.
Although acceleration has been studied thoroughly as an educational practice for the gifted, early entrance to college specifically has been overlooked. Furthermore, a large portion of this research pertained to early college entrance programs, which provide resources that many early college entrants may not have. The lived experiences and perceptions of radically early college entrants (3 or more years advanced) were explored through interviews and heuristic inquiry. The interviews addressed affective aspects of early college foremost, with additional discussion of academic experiences, college choice, and career outcomes. Findings support that radically early college entrants are happy with their choice overall, although more specific findings elaborate on the benefits and limitations of early college, possible regrets, and the social issues this population faces.